"ENVIRONMENTAL AWARENESS AMONG UNIVERSITY STUDENTS: A STUDY" (WITH REFERENCE TO HIMACHAL PRADESH UNIVERSITY): “विश्वविद्यालयीन विद्यार्थियों में पर्यावरण जागरूकता: एक अध्ययन” (हिमाचल प्रदेश विश्वविद्यालय के संदर्भ में) - dhol, Jyoti (International Journal of Research -GRANTHAALAYAH, 2015)
Today we have entered the 21st century, in which science and technology are playing an important role. This progress has solved many mysteries of another universe. The same has provided many other pleasures of human beings. The environment has always been helpful in these human progress and development, but in the race for this development, we have neglected the environment and exploited it uncontrollably. In the greed for immediate benefits, man himself has put his future in a long-term crisis. As a result, the source of life, the environment is becoming increasingly degraded. This project work is presented in this context. The Supreme Court of India feels that every citizen of India should understand environmental information and accountability and give suggestions for environmental improvement. In the research work, the primary data was compiled by filling the questionnaire using the deviation system (च स ड ड ड जीव जीव जीव जीव जीव तथा तथा तथा सर्वेक्षण) and information was obtained by surveying the university. Primary as well as secondary data were used for research work. Selection of the field After selecting five departments (Arts, Commerce, Research, Computer and other departments) of Himachal Pradesh University, data is obtained by filling a questionnaire from 5 to 5 students of each department. A questionnaire was prepared to understand environmental problem and problem related awareness. Conclusions and suggestions related to the problem are given. Word Key - Student and environmental awareness, environmental awareness. आज हम 21वीं सदी मे प्रवेष कर चुके है, जिसमें विज्ञान और प्रौद्योगिकी एक महत्वपूर्ण भूमिका निभा रहे है। इस प्रगति ने जहां एक और ब्रह्माण्ड के अनेक रहस्यों को सुलझाया है । वही दूसरी और मानव का अनेकानेक सुख सुविधाएं प्रदान की है। इन मानवीय प्रगति एवं विकास मे पर्यावरण तो सदैव सहायक रहा है, परन्तु इस विकास की दौड़ मे हमने पर्यावरण की उपेक्षा की और उसका अनियन्त्रित शोषण किया है। तात्कालिक लाभों के लालच मे मानव ने स्वयं अपने भविष्य को दीर्घकालीन संकट मे डाल दिया है। परिणामस्वरूप जीवन के स्त्रोत पर्यावरण का अवनयन होता जा रहा है। इसी परिपेक्ष्य मे यह परियोजना कार्य प्रस्तुत है। भारत का सर्वाेच्च न्यायालय यह महसूस करता है कि भारत का हर नागरिक पर्यावरण जानकारी व जवाबदारी को समझे व पर्यावरण सुधार संबंधी सुझाव दे । शोध कार्य में देव निदर्षन;ैंउचसपदह डमजीवकद्धप्रणाली का प्रयोग कर प्रष्नावली भरवाकर प्राथमिक आंकड़ों का संकलन किया गया तथा विष्वविद्यालय का सर्वेक्षण कर जानकारी प्राप्त की गई। शोध कार्य हेतु प्राथमिक के साथ-साथ द्वितीयक आंकड़ों का उपयोग किया गया। कार्यक्षेत्र का चयन हिमाचल प्रदेष विष्वविद्यालय के पांच विभागों (आर्टस्, काॅर्मस, र्साइंस, कम्प्यूटर व अन्य विभागों) का चयन कर प्रत्येक विभाग के 5-5 विद्यार्थियों से प्रष्नावली भरवाई जाकर आंकड़े प्राप्त किये गये है। पर्यावरण समस्या एवं समस्या से निदान पाने सम्बन्धि जागरूकता को समझने के लिए प्रष्नावली तैयार की गई। समस्या से संबंधित निष्कर्ष एवं सुझाव दिए गए है। शब्द कुंजी-विद्यार्थी एवं पर्यावरण जागरूकता, पर्यावरण जागरूकता।